2012
DOI: 10.1021/ma2024045
|View full text |Cite
|
Sign up to set email alerts
|

Bithiophenesilane-Based Dendronized Polymers: Facile Synthesis and Properties of Novel Highly Branched Organosilicon Macromolecular Structures

Abstract: The synthesis of two novel bithiophenesilane-based dendronized polymers by a chain growth Kumada polymerization, their molecular properties in dilute solutions and thermal properties in the bulk are described and compared with those of bithiophenesilane dendrimers. GPC equipped with a dual light scattering detector has shown that the polymers exhibit narrow polydispersity indices (PDI = 1.22–1.23) and have a weight-average polymerization degree of 44 for P1 and 30 for P2, which correspond to 88 and 120 bithiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 43 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…From the value of the onset reduction potentials (4 red ) and the onset oxidation potentials (4 ox ), the LUMO and HOMO energy levels of these molecules were calculated as shown in Table 2, according to the equations of LUMO ¼ Àe(4 red + 4.40) (eV) and HOMO ¼ Àe(4 ox + 4.40) (eV). 34 The LUMO energy levels were determined to be À3.46 eV for N(Ph-1T-DCN-Me) 3 , À3.41 eV for N(Ph-2T-DCN-Me) 3 , À3.41 eV for N(Ph-2T-DCN-Hex) 3 , and À3.40 eV for N(Ph-3T-DCNHex) 3 by the above-mentioned equation, revealed that the 3 , N(Ph-2T-DCN-Me) 3 , N(Ph-2T-DCN-Hex) 3 , and N(Ph-3T-DCN-Hex) 3 in ODCB solution (a) and in the film (b).…”
Section: Photophysical and Electrochemical Propertiesmentioning
confidence: 99%
“…From the value of the onset reduction potentials (4 red ) and the onset oxidation potentials (4 ox ), the LUMO and HOMO energy levels of these molecules were calculated as shown in Table 2, according to the equations of LUMO ¼ Àe(4 red + 4.40) (eV) and HOMO ¼ Àe(4 ox + 4.40) (eV). 34 The LUMO energy levels were determined to be À3.46 eV for N(Ph-1T-DCN-Me) 3 , À3.41 eV for N(Ph-2T-DCN-Me) 3 , À3.41 eV for N(Ph-2T-DCN-Hex) 3 , and À3.40 eV for N(Ph-3T-DCNHex) 3 by the above-mentioned equation, revealed that the 3 , N(Ph-2T-DCN-Me) 3 , N(Ph-2T-DCN-Hex) 3 , and N(Ph-3T-DCN-Hex) 3 in ODCB solution (a) and in the film (b).…”
Section: Photophysical and Electrochemical Propertiesmentioning
confidence: 99%
“…Organosilicon dendrimers containing aromatic and heterocyclic fragments, benzothiadiazole, anthracene, thienyl, oxazole, fluorene, and thiophene, as well as liq uid crystalline dendrimers, were synthesized and char acterized [212,213,[217][218][219][220][221][222][223].…”
Section: Dendrimersmentioning
confidence: 99%
“…722 The narrow molecular-mass distribution (1.22 ± 1.23), high molecular masses and the use of nickel catalyst indi-cate that the process follows a living polymerization mechanism. Thus, it was demonstrated that bulky monomers can also be polymerized by this mechanism.…”
Section: Scheme 158mentioning
confidence: 99%